Personnel, institutions, and power: Revisiting the concept of executive personalisation - Mariana Llanos; David Kühn; Thomas Richter; Martin Acheampong; Esther E. Song; Emilia Arellano (German Institute of Global and Area Studies (GIGA), 2024)
Evidence points to an increasing personalisation of political power by chief executives in recent years. It is often argued that such personalisation contributes to the current trend of autocratisation and the global decline of democracy. Yet our understanding hereof remains fractured, not least because there are a plethora of tacit understandings, definitions, and concepts vis-à-vis what political personalisation is. While potentially occurring in both autocracies and democracies, the scholarship is still too often siloed according to regime type. We thus develop a framework defining the phenomenon as a process in which the chief executive personalises power in policymaking and policy implementation by weakening the constraining capacities of relevant actors. The "personalisation of executive power" (PEXP) runs through three distinct mechanisms: personnel management, institutional engineering, and power arrogation. We illustrate the usefulness of our conceptual framework with four case studies during the COVID-19 pandemic: El Salvador, Ghana, South Korea, and Zimbabwe.
Keywords: 300; autocracy; democracy; executive; decision making; concentration of political power; personalisation; Covid-19 pandemic